IDENTIFICATIONS OF CARCASS CHARACTERISTIC FOR ESTIMATING THE COMPOSITION OF BEEF CARCASS - Hafid, H.; Gurnadi, R.E.; Priyanto, R.; Saefuddin, A. (Journal of the Indonesian Tropical Animal Agriculture, 2010)
The research aimed to identify carcass characteristic that can be used for estimating composition ofbeef carcass. It was used 165 Brahman crossbred cattle in this research. Carcass characteristics wereweight of a half cold carcass (WC) ranged from 96 to 151 kg, loin eye area (LEA) ranged from 22.09 to304.8 mm2, 12th rib fat thickness (FT12) ranged from 0.80 to 2.90 mm, meat ranged from 53.55 to 90.10kg and carcass fat ranged from 5.54 to 39.72 kg. Result showed that a half weight cold carcass as asingle indicator major may be used to predict meat weight and carcass fat with regression linearequation: Meat (kg) = 10.64 + 0.49 WC (R2=0.728 and SE=3.58), and Fat (kg) = -21.70 + 0.36 WC**(R2=0.582 and SE=3.65). Multiple regression to predict meat weight based on fat percentage of kidney,pelvic and heart (KPH) was Meat (kg) = 7.99 + 0.58 WC** - 4.41 KPH** (R2=0.751 and SE=3.43).